Surgical reconstruction of a giant left ventricular aneurysm with prior unloading using a microaxial pump. (16th May 2022) - Medina Estrada, Marta L; Silaschi, Miriam C; Charitos, Efstratios I; Treede, Hendrik
Abstract: A 46-year-old male patient presented with cardiac decompensation due to a giant left ventricular aneurysm combined with a severely reduced left ventricular function after a silent myocardial infarction. Left ventricular unloading was performed with a microaxial pump as a bridge to surgery. Myocardial function in the basal segments was preserved and surgical ventricular reconstruction was performed successfully. Abstract : A 46-year-old male was admitted to hospital due to cardiac decompensation New York Heart Association (NYHA) functional class IV 2 weeks after silent myocardial infarction complicated by postinfarction left ventricular aneurysm resulting in severely reduced left ventricular function (LVEF).